Oxyvanite V3O5: A new intercalation‐type anode for lithium‐ion battery. Issue 2 (22nd May 2019) - Chen, Dong; Tan, Huiteng; Rui, Xianhong; Zhang, Qi; Feng, Yuezhan; Geng, Hongbo; Li, Chengchao; Huang, Shaoming; Yu, Yan
Abstract: In the present study, V3 O5 microcrystals that synthesized via vacuum calcination are employed as anodes for lithium‐ion batteries (LIBs) for the first time. Despite the widely observed sluggish reaction kinetics and poor cycling stability in most micro‐sized transition metal oxides, the V3 O5 microcrystals exhibit excellent rate capability (specific capacities of 144 and 125 mAh g −1 are achieved at extremely high current densities of 20 and 50 A g −1, respectively) and long‐term cycling performance (specific capacity of 117 mAh g −1 is sustained over 2000 cycles at 50 A g −1 ). It is ascribed to the three‐dimensional open‐framework structure of the V3 O5 microcrystals as a major factor in dictating the fast reaction kinetics (lithium diffusion coefficient: 10 −9 cm 2 s −1 ). In addition, significant insight into the reaction mechanism of the V3 O5 microcrystals in concomitant its phase evolution are obtained from ex‐situ XRD study, revealing that the V3 O5 microcrystals undergo intercalation reaction with insignificant structural change in response to lithiation/delithiation. Abstract : V3 O5 microcrystals are employed as an intercalation‐type anode for lithium‐ion battery for the first time. It demonstrates an excellent rate capability (eg, showing a capacity of 125 mAh g −1 at an ultrahigh current density of 50 A g −1 ) and a long‐term cycling stability (117 mAh g −1 is still sustained after 2000 cycles at 50 A g −1 ).